Developing Learning Multimedia Based on Geographical Information System to Improve Studentsâ Spatial Ability in Flood-Disaster Mitigation - Muryani, Chatarina; Nugraha, Setya; AS, Taufik Lilo; Soegiyantoa, H (Proceeding of International Conference on Teacher Training and Education, 2016)
The research was aimed to: (1) define the students and teachersâ need toward flood-disaster learning multimedia; (2) develop flood-disaster learning multimedia based on Geographical Information System (GIS), and (3) find out the effectiveness of the developed media in improving the studentsâ ability in flood-disaster mitigation. The research used Educational Research and Development with three major stages, namely: Define, Design, and Develop. Define Stage consists of literature study and need analysis. Design Stage consists of product specification, material collection, product designing, and product validation. Develop Stage consists of field testing and product experiment. The setting of the research was in Surakarta district. The result of the research were: (1) from the need analysis, it could be revealed that 72% of the students stated that Geography was a boring subject, 69% of the teachers did not have any experience dealing with multimedia for teaching, and 85% of the students needed a more innovative Geography lesson; (2) the flood-disaster learning multimedia was designed in a form of text, animation, film, and map. The novelty of the proposed product was that more than 75% of the material in the developed product was collected through live-field recording, while the text and animation was originally designed by the researchers. The product consisted of several parts, namely: introduction, flood-disaster cause factors, types of flood, flood spatial, flood-disaster effect, and flood mitigation; and (3) experimental test was done to find out the effectiveness of the designed product in improving the studentsâ ability in flood-disaster mitigation, and the result showed that the product was effective.